Analisis Literasi Informasi Terhadap Mahasiswa Ilmu Perpustakaan dan Informasi Islam Anggakatan 2022-2023 Melalui Penelusuran Informasi - Sholikhah, Siti; Yuka Dita Prasetya, Yuka; Vratiwi, Deli; Rizkyantha, Okky (Jurnal Tadwin, 2024)
This research is entitled "Information Literacy Analysis of Islamic Library and Information Science Students Class of 2022-2023 through Information Search". The aim of this research is to find out how the information literacy skills of Islamic Library and Information Science students class 2022-2023 are in searching for information through information browsing. The method in this research uses descriptive methods with a quantitative approach. The data collection technique uses a questionnaire. The population in this research is students of Islamic Library and Information Science, Faculty of Ushuluddin Adab and Da'wah, Curup State Islamic Institute, class of 2022-2023. The questionnaire was distributed to 40 respondents. The results obtained from this research show that the information literacy abilities of Islamic Library and Information Science Undergraduate Study Program students class of 2022-2023 through information searching can be categorized as high, namely with a score of 3.10. In the empowering method 8, it can be seen from the processes of identifying, exploring, selecting, organizing, creating, presenting, assessing and applying.